MEKANISME PASAR, DEMOKRASI PERWAKILAN DAN KRISIS EKONOMI - Yuni Prihadi Utomo (Muhammadiyah University Press, 2000)
The economic crisis that attacks Indonesia has yet to be solved even that several policies taken by the government to overcome the problem are not in accordance with the reform spirit and unpopular. In order that we can understand about the problem more well, then we need to reobserve the root of this economic crisis problem. This observation uses the view of capitalist economics theory with the discussion in the aspect of market mechanism and the democracy of delegation theory. In the discussion, it is mentioned that the capitalist economic system wishes to have a certain political system that allows the people s preference to the social welfare level to be optimal for itself which it is accommodated by their delegation in government. In reality, the commitment of the capitalist economic system is not the healthy democracy tradition system. Thus, the market mechanism does not yield an optimal solution for large people's welfare.